Politeness Strategies The Use of Bald-On Record in The “Moana” Cartoon Movie - Intan Safitri; Etika Dewi Kusumaningtyas (Universitas An Nuur, 2022)
This research in title “Politness strategies the use Bald-on Record in the MOANA movie. The problems of this research are: What kinds of Politeness Strategies used Blad-on record by the character in “Moana” & What are the functions of Politeness Strategies Bald-on Record used by the main character in “Moana” movie. The researcher used descriptive qualitative method. The purpose of this research is to identify, classify, analyze the function and types of politeness strategies in used that can be shown in the conversation in the animation movie. In collecting data, the writer concentrates the utterance‟s which contains the politeness strategies produced by the main character in the movie. The result of the research, there are 4 strategies that are used by these 2 characters; bald-on record, positive politeness, negative politeness, and off record. This research foccus in politeness strategies use bald-on record.